The Influence of Communication and Job Satisfaction on Employee Performance in the Context of Organizational Culture at the Medan Amplas Sub-district Office - Harahap, Baran Enda; Lubis, Mirna; Cipta, Hendra; Paramita, Esti; Nugraha, Dian; Sri Rahayu (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the influence of communication, job satisfaction, and organizational culture on employee performance at the Medan Amplas Sub-district Office. The research used a quantitative method with a survey approach, involving 50 respondents. The data were analyzed using multiple linear regression. The results of the study show that communication, job satisfaction, and organizational culture partially and simultaneously have a significant effect on employee performance. Communication has the greatest influence compared to other variables. The determination coefficient shows that 75.4% of the variation in employee performance can be explained by these three variables. The implications of this study emphasize the importance of improving the quality of communication, job satisfaction, and organizational culture in order to improve employee performance in the government environment.